Export behavior of Philippine export entrepreneurs - Umali, Jaime O. (Animo Repository, 1999)
Dr. Jaime Umali of the Business Management Department talked on Export Behavior of Philippine Export Entrepreneurs.The activity is also part of University Week '99 celebration.